2022
DOI: 10.1002/slct.202104450
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐Opening Copolymerization of Cyclic Anhydrides and Epoxides by bis(amidinate)tin(II) Complex via Binary Catalyst System

Abstract: Bis(amidinate) tin(II) complex (1) was reported as active catalyst for ring‐opening copolymerization of cyclic anhydrides and epoxides via a binary catalyst system. Polymerizations of six combinations of epoxides and cyclic anhydrides were carried out giving highly alternating poly(anhydride‐alt‐epoxide) with narrow dispersities, except for cyclohexene oxide where significant amount of ether linkage up to 62 % was observed. This ether linkages could be diminished by increasing the amount of cocatalyst to over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“… 38 , 41 Additionally, Thumrongpatanaraks et al observed a notable difference in the reactivity between MA and SA with propylene oxide (PO) when using the same bis(amidinate)tin(II) catalyst where the poly(PO- co -MA) polyester was afforded at 80% conversion in only 1 h, whereas SA required 8 h to form poly(PO- co -SA) with a similar conversion. 37 In our case, the successful preparation of poly(EOO- co -MA) was performed under the same reaction conditions as poly(EOO- co -PA), although the synthesis of poly(EOO- co -SA) required more extreme reaction conditions (reflux in toluene for 72 h), as can be seen in Table 2 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“… 38 , 41 Additionally, Thumrongpatanaraks et al observed a notable difference in the reactivity between MA and SA with propylene oxide (PO) when using the same bis(amidinate)tin(II) catalyst where the poly(PO- co -MA) polyester was afforded at 80% conversion in only 1 h, whereas SA required 8 h to form poly(PO- co -SA) with a similar conversion. 37 In our case, the successful preparation of poly(EOO- co -MA) was performed under the same reaction conditions as poly(EOO- co -PA), although the synthesis of poly(EOO- co -SA) required more extreme reaction conditions (reflux in toluene for 72 h), as can be seen in Table 2 .…”
Section: Resultsmentioning
confidence: 97%
“…Given the challenge of preparing new bio-based materials, other cyclic anhydrides, such as MA and SA, were used as starting materials together with EOO to obtain the corresponding poly­(EOO- co -MA) and poly­(EOO- co -SA) polyesters, respectively (Table ). It is reported that in some cases for both MA and SA, there are more difficulties in the formation of polyesters by the ROCOP process. , However, under relatively moderate reaction conditions, MA and SA anhydrides have also been used as substrates for the creation of various polyesters, which is directly related to the activity of the applied catalytic systems. , Additionally, Thumrongpatanaraks et al observed a notable difference in the reactivity between MA and SA with propylene oxide (PO) when using the same bis­(amidinate)­tin­(II) catalyst where the poly­(PO- co -MA) polyester was afforded at 80% conversion in only 1 h, whereas SA required 8 h to form poly­(PO- co -SA) with a similar conversion . In our case, the successful preparation of poly­(EOO- co -MA) was performed under the same reaction conditions as poly­(EOO- co -PA), although the synthesis of poly­(EOO- co -SA) required more extreme reaction conditions (reflux in toluene for 72 h), as can be seen in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal complexes play an important role to control catalytic activity and selectivity in the polymerizations . In the past decades, several metal complexes such as zinc, magnesium, ,,, manganese, iron, , tin, chromium, ,, cobalt, ,− and aluminum ,,,,, were reported to efficiently catalyze ROCOP of epoxides and cyclic anhydrides. Among the reported catalysts, the salen-based ligand systems were extensively explored due to simple ligand synthesis and diverse electronic and steric modifications of the substituents and diamine backbones. , The salen-based system was demonstrated to have high activities for ROCOP in the presence of nucleophilic cocatalysts such as bis (triphenylphosphine)­iminium chloride (PPNCl), 4-dimethylaminopyridine (DMAP), or tetrabutylammonium bromide (TBAB). ,, In 2015, Coates and colleagues reported the copolymerization of propylene oxide (PO) and terpene-based cyclic anhydrides (TBAs) catalyzed by chromium, cobalt, and aluminum (salph) complexes .…”
Section: Introductionmentioning
confidence: 99%
“…26 The new polymer sequence ABB contains double insertions of epoxides that can improve the thermal properties of the polymers. Other tin( ii ) catalysts such as Sn(OMe) 2 , 27 amine Schiff-base tin( ii ), 28 and bis (amidinate)tin( ii ) 29 were also reported revealing preferences for multiple insertions of epoxides leading to poly(ester-ether). Trinuclear Co( iii ) complexes were shown to promote consecutive epoxide insertions resulting in polymers having single-glass transition and tunable properties.…”
Section: Introductionmentioning
confidence: 99%